Adherence to the planetary health diet index and metabolic dysfunction-associated steatotic liver disease: a cross-sectional study - Qiu, Xin; Shen, Shuang; Jiang, Nizhen; Lu, Donghong; Feng, Yifei; Yang, Guodong; Xiang, Bangde (Frontiers in Nutrition, 2025)
BackgroundsAdherence to the Planetary Health Diet Index (PHDI) has been shown to benefit both individual health and the planet. However, its impact on Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) remains unclear. This study aimed to investigate the relationship between PHDI adherence and the MASLD risk.MethodsWe analyzed a cohort of 15,865 adults (aged ≥18 years) using data from the National Health and Nutrition Examination Survey (NHANES, 2005–2018). The PHDI was derived from 24-h dietary assessments and comprised the scores of 15 food groups. Multivariate logistic regression was used to investigate the association between PHDI and MASLD, while restricted cubic spline (RCS) regression and threshold analysis were employed to explore potential non-linear relationship. Subgroup analyses were conducted to assess the influence of various demographic and clinical characteristics on the observed associations. Mediation analysis was performed to evaluate the indirect effect of PHDI on MASLD, and weighted quantile sum (WQS) regression was used to assess the influence of individual PHDI nutrients on MASLD.ResultsAmong the cohort, 6,125 individuals were diagnosed with MASLD. Multivariate logistic regression revealed that a higher quintile of PHDI was significantly associated with reduced MASLD risk in the fully adjusted model (OR = 0.610, 95%CI 0.508–0.733, p < 0.001). Notably, nonlinear relationships between PHDI and MASLD risk were observed through RCS analysis (p = 0.002). Subgroup analyses indicated that PHDI was particularly effective in reducing MASLD risk among females, those with higher education attainment, and those living with a partner. WQS regression identified saturated fatty acids as the most significant factor contributing to MASLD risk (weight = 0.313). Additionally, BMI and waist circumference (81.47 and 87.66%, respectively) partially mediated the association between PHDI and MASLD risk, suggesting that the effect of PHDI on MASLD operates, in part, through its impact on BMI and waist circumference. The association between PHDI and MASLD remained robust across multiple sensitivity analyses.ConclusionOur findings indicate that adherence to PHDI is linked to a lower risk of MASLD, providing crucial insights for strategies aimed at mitigating the MASLD epidemic while simultaneously fostering environmental sustainability.